3D printed titanium scaffolds with homogeneous diamond-like structures mimicking that of the osteocyte microenvironment and its bone regeneration study. (28th October 2020) - Pei, Xuan; Wu, Lina; Zhou, Changchun; Fan, Hongyuan; Gou, Maling; Li, Zhengyong; Zhang, Boqing; Lei, Haoyuan; Sun, Huan; Liang, Jie; Jiang, Qing; Fan, Yujiang; et al.
Abstract: Biofabrication of personalized titanium scaffold mimicking that of the osteocyte microenvironment is challenging due to its complex geometrical cues. The effect of scaffolds geometrical cues and implantation sites on osteogenesis is still not clear. In this study, personalized titanium scaffolds with homogeneous diamond-like structures mimicking that of the osteocyte microenvironment were precisely designed and fabricated by selected laser melting method. The effects of different geometric cues, including porosity, pore sizes and interconnection properties, on cellular behavior were investigated. Biomimetic mechanical properties of porous titanium alloy scaffold were predesigned and simulated by finite element analysis. In vitro experiment revealed that homogeneous diamond-like structures mimicking that of the osteocyte microenvironment triggered osteocyte adhesion and migration behavior. Typical implantation sites, including rabbit femur, beagle femur, and beagle skull, were used to study the implantation sites effects on bone regeneration. In vivo experimental results indicated that different implantation sites showed significant differences. This study helps to understand the scaffolds geometrical microenvironment and implantation sites effects on osteogenesis mechanism. And it is beneficial to the development of bone implants with better bone regeneration ability.